2007
DOI: 10.1002/dev.20240
|View full text |Cite
|
Sign up to set email alerts
|

Foster mother care but not prenatal morphine exposure enhances cocaine self‐administration in young adult male and female rats

Abstract: The present study was designed to investigate cocaine self-administration in adult male and female rats exposed prenatally to morphine. Pregnant dams were injected two times a day with either saline, analgesic doses of morphine or no drug at all (controls) on gestation Days 11-18. One day after birth, litters were cross-fostered such that control dams were paired with one another and their litters were crossed; saline- and morphine-treated dams were paired and half of each saline litter was crossed with half o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…Although no differences were reported in females, only one conditioning regimen was examined, and thus it is possible that sensitivity of females to stimulants may be affected under different conditioning parameters. In 268 any case, this sex-dependent effect is interesting in light of other results showing increased vulnerability to cocaine self-administration in male rats, but not female rats, subjected to neonatal stress from crossfostering (Vathy et al, 2007). Increases in locomotor activity to amphetamine also occur in male rats artificially reared in isolation with low levels of maternal-like stimulation, but not with high levels of stimulation (Lovic et al, 2006).…”
Section: B Social Influencesmentioning
confidence: 65%
“…Although no differences were reported in females, only one conditioning regimen was examined, and thus it is possible that sensitivity of females to stimulants may be affected under different conditioning parameters. In 268 any case, this sex-dependent effect is interesting in light of other results showing increased vulnerability to cocaine self-administration in male rats, but not female rats, subjected to neonatal stress from crossfostering (Vathy et al, 2007). Increases in locomotor activity to amphetamine also occur in male rats artificially reared in isolation with low levels of maternal-like stimulation, but not with high levels of stimulation (Lovic et al, 2006).…”
Section: B Social Influencesmentioning
confidence: 65%
“…Vathy et al studied the later consequences of disrupted maternal care by morphine-treated mothers for offspring (Vathy et al, 2007). The researchers found that disrupted maternal behavior was more important than prenatal drug exposure itself in rewarding cocaine self-administration in adulthood, especially in female offspring.…”
Section: Maternal Behavior In Animalsmentioning
confidence: 99%
“…Rats with prenatal methamphetamine exposure (5mg/kg/day) show improvement in maturation tests when fostered to drug-naïve dams (Pometlova et al 2009). Similarly, while non-fostered rat offspring with in utero saline or morphine exposure (5mg/kg injection GD11-13, 10mg/kg GD14-18) did not exhibit higher operant response rates for cocaine (0.5mg/kg/inj) compared to controls, fostering itself increased responding for cocaine regardless of prenatal treatment group (Vathy et al 2007). In our previous study, cross-fostering of offspring with prenatal nicotine exposure (3mg/kg/day) did not affect the increase in the dopaminergic response to a nicotine injection.…”
Section: Discussionmentioning
confidence: 99%